Effect of ease of use perception on user interest with attitude as mediator: A case study of Tokopedia users in Klungkung - Ni Kadek Evitasari; Agus Wahyudi Salasa Gama; Ni Putu Yeni Astiti (Universitas Pendidikan Nasional, 2024)
This study aimed to determine the influence of the perception of ease of use on user interest with usage attitude as a mediating variable in Tokopedia e-commerce. The population in this study consisted of all Tokopedia e-commerce users in Klungkung Regency. The sample was selected using a purposive sampling technique, resulting in a sample size of 90 people. Data collection was conducted through Google Forms, and the data analysis technique employed SEM-PLS. The results of the study showed that the perception of ease of use had a positive and significant effect on interest in using Tokopedia e-commerce. The perception of ease of use also had a positive and significant effect on the attitude toward using Tokopedia e-commerce. Usage attitudes had a positive and significant effect on interest in using Tokopedia e-commerce. Additionally, the perception of ease of use had a positive and significant effect on interest in using Tokopedia e-commerce through usage attitude as a mediating variable. This research was expected to contribute in the form of suggestions or inputs to interested parties as a consideration for decision-making in addressing problems related to declining user interest.